Reliable anatomical landmarks for minimizing leg-length discrepancy during hip arthroplasty using the lateral transgluteal approach for femoral neck fracture. Issue 11 (November 2017) - Kim, Jeung II; Moon, Nam Hoon; Shin, Won Chul; Suh, Kuen Tak; Jeong, Jae Yoon
Abstract: Background: The purpose of this study was to describe our experience of a preoperative templating technique, and to investigate the most reliable anatomical reference to minimize leg length discrepancy (LLD) during hip arthroplasty using the lateral transgluteal approach for femoral neck fractures. We hypothesized that the medial fracture tip and greater trochanter would be viable alternative anatomical References Methods: A total of 156 hip arthroplasty cases were enrolled in the present study (103 women, 114 hemiarthroplasties, 42 total hip arthroplasties). Preoperative acetate overlay templating was conducted based on pelvic anteroposterior radiographs. Three different anatomical references were used to determine the bony resection level, including the uppermost point of the lesser trochanter, uppermost point of the greater trochanter, and medial fracture tip. The accuracy of preoperative templating and the reliability of each anatomical reference for minimizing LLD were assessed. Results: Significant differences in postoperative LLD after hip arthroplasty between the three groups were identified. Post-hoc analysis showed that postoperative LLD in group A was significantly larger than that in groups B or C in hip arthroplasty. Conclusion: The results of this study suggest that the use of the lesser trochanter as an anatomical reference to determine the level of femoral neck osteotomy should be discouraged, and that the medial fracture tip and greater trochanter may be better alternatives when using the lateral transgluteal approach.